Answer:
g(1) = 1
Step-by-step explanation:
Given the piecewise function:
![g(x)=\mleft\{\begin{aligned}-343x,\text{ x=-2} \\ (x-1)(x+2),\text{ x= -1} \\ x^3-x^2+1,\text{ x}\\e-2,\text{ -1}\end{aligned}\mright.](https://img.qammunity.org/2023/formulas/mathematics/college/j7vgakr94gutrcv5sljwvyzh9zqwydvoug.png)
To find the value of g(1), this means x = 1
Looking at the piecewise function, the only function that satisfies the condition x = 1
is
![x^3-x^2+1](https://img.qammunity.org/2023/formulas/mathematics/college/gz1uw7zb14e9kasbe0bdags28d3io80ukp.png)
Because it is for all x different from -2 and -1, and x = 1 is.
Substituting x = 1 in
![x^3-x^2+1](https://img.qammunity.org/2023/formulas/mathematics/college/gz1uw7zb14e9kasbe0bdags28d3io80ukp.png)
we have:
![\begin{gathered} 1^3-1^2+1 \\ \\ =1-1+1 \\ \\ =1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o5zvsh0ywmkvzjpnlipmf9hch7o6n3zw1d.png)
Therefore, g(1) = 1